An Optimized E/CRC Erosion Model of Round Particles for Hydraulic Spool Valves With Euler–Lagrange Two-Phase Simulation. Issue 5 (3rd September 2021) - Du, Run; Zhou, Yongjie; Zhang, Anying; Du, Zhihua; Zhang, Xiaoyu; Yuan, Xinlu
Abstract: Solid particles mixed in the oil cause erosion of hydraulic spool valves, and these valves may fail in severe erosion. In this article, with the help of the Euler–Lagrange solver, a numerical model of the solid–liquid two-phase flow is established for the spool valves, in which the standard k-ε model is used for the turbulent flow. With a comparison of seven different erosion models, the E/CRC erosion model is the closest one to the experiment data. Based on the numerical model and the experiment data, an optimized E/CRC erosion model with a new impact angle function for complete round particles is proposed for the spool valves. It is observed that there is better agreement between the optimized model and the experimental values. In addition, the relationships between the erosion rate and the main influencing factors are revealed, including the particle size, particle concentration, differential pressure, flow direction, spool opening, and oil viscosity.